The role of science communication in popularizing ethnoastronomy - Fernanda Michelini; Marina Queiroz; Vitor Acioly (Education and Development Research, 2025)
Ethnoastronomy is a scientific field that explores the astronomical knowledge of different cultures through their traditions, offering perspectives distinct from conventional Western astronomy. This study examines the interplay between Science Communication and Ethnoastronomy, using Vygotsky's sociocultural theory as a foundation. A literature review was conducted to identify concepts that validate the interrelation of these areas, highlighting how Science Communication can foster fresh understandings. Moreover, this research delves into indigenous astronomical perspectives, specifically those of the Karajá Xambioá and Tupi-Guarani peoples, and presents an educational game designed for a diverse age group in an informal learning setting. The objective is to investigate how Science Communication, particularly through Cultural Communication, can effectively facilitate the dissemination of astronomical knowledge from various cultural backgrounds, with a focus on Brazil's indigenous peoples, thereby broadening perspectives and understanding. With this, materials were developed that brought indigenous culture closer to science teaching immersed in traditional and Western culture, with the aim of reducing the distances between different cultures.